Analisis Pengaruh Distribusi Pendapatan Terhadap Pertumbuhan Ekonomi Masyarakat Kota Manado. - Arnold Pontoh Sawotong; Jen Tatuh; Caroline E. Pakasi (COCOS, 2013)
ABSTRACTThe greater the difference in the distribution of the "pie" of development, the greater the disparity in income distribution that occurred. Indonesia is classified in the developing world can not be separated from the issue. This research aims: to analyze the effect of income distribution on economic growth in the city of Manado.The research methodology used is quantitative methods. Data used in this study is secondary data. The data will be used are time series data from 2003 to 2012. Data obtained from various sources such as data from Bank Indonesia, BPS Manado City is located in Manado and other agencies involved in the city of Manado. Data were analyzed through the method of Ordinary Least Squre (OLS).The results showed that 1) the distribution of factor income residents of the city of Manado as measured by the Gini ratio has a significant influence on the rate of economic growth of the city of Manado with a positive coefficient. This indicates unequal distribution of income goes in line with the economic growth of Manado, where the higher the level of inequality of income distribution, economic growth in the city of Manado will be increasing as well. 2 ) The effect of other variables that affect the economic growth of Manado include : first , the population growth rate factor of Manado has a significant negative effect on the rate of economic growth , which means that the population growth rate increases, the rate of economic growth of the city of Manado will decrease . Second , government spending Manado factors have a positive effect , but no significant effect on the rate of economic growth in the city of Manado . It means if government spending increases the city of Manado Manado economic growth rose . Third , domestic investment and significant negative effect on the rate of economic growth , which means that if investment in the country also decreased the rate of economic growth of the city of Manado will decrease . Fourth , foreign investment and significant positive effect on economic growth of the city of Manado . It means if the foreign investment increases, the rate of economic growth of the city of Manado increase as well .It can be concluded from the distribution of income affect the economic growth of the city of Manado. Recommended to the government that in the effort to create a more equitable distribution of income, the government should establish and empower the entrepreneurial skills of the people who experience barriers to productive economic activities independently. This work is done so that the poor have a fixed income. The initial step of this program can be reached through the stimulus of working capital to the poor or providing education training (training) aimed at improving the practical economic independence. Current population growth is increasing the government should make a return enterprising in promoting family planning program, and the government should create a program that limits the entry of workers from other areas, so that the density of the city of Manado will not increase.Key Word : Income Distribution, Economic growth